Da cultura afirmativa à dessublimação repressiva: a dialética da sublimação em Herbert Marcuse - Schang, Renata Aparecida Martinussi (2023)
This work is dedicated to the dialectic of sublimation present in the work of Herbert Marcuse. This project is carried out through the so-called Freudo-Marxism, whose trajectory is considered here in three typical steps of dialectical materialism. The first step highlights the separation between art and the material conditions of existence, from Antiquity to the transcendent character of the affirmative culture of the 19th century. The second step introduces Freudo-Marxism and, through it, Marcuse's attempt to improve the Marxist program by locating possibilities for emancipation in the instinctual and sensitive spheres, as well as presenting his project for a self-sublimation of sexuality. The third step shows how the repressive desublimation of culture and sexuality has weakened the sensitive functions of the human being and compromised the political objective of happiness under the laws of the performance principle.